Stimulated Thyrotropin (TSH) Levels Were Inversely Correlated with Age - Bi WK; Xu H; Tian ZH; Teng W; Zheng GW; Yin QQ (International Journal of General Medicine)
Wen-Kai Bi,1 Hua Xu,2 Zhen-Hua Tian,3 Wei Teng,4 Gui-Wen Zheng,1 Qing-Qing Yin5 1Department of Nuclear Medicine, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 2Shizhong District Center for Disease Control and Prevention, Jinan, Shandong, People’s Republic of China; 3Department of Endocrinology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 4Department of Nuclear Medicine, Laizhou People’s Hospital, Yantai, Shandong, People’s Republic of China; 5Department of Geriatric Neurology, Shandong Provincial Hospital affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of ChinaCorrespondence: Qing-Qing Yin, Shandong Provincial Hospital affiliated to Shandong First Medical University, No. 324 Jingwu Road, Jinan, Shandong, 250021, People’s Republic of China, Email yinqingqing@sdfmu.edu.cnPurpose: Serum Thyrotropin (TSH) levels in the elderly have been reported to be inconsistent in different studies. One of the difficulties in determining the effect of aging on TSH levels is that TSH levels are influenced by various factors, including thyroid-related factors. Therefore, this study aimed to assess the effect of aging on TSH levels while controlling for thyroid factors.Patients and Methods: This study included a total of 343 subjects, who underwent thyroidectomy, levothyroxine (LT4) supplementation and withdraw. All participants were divided into young(18– 44year old), middle(45– 59year old), and old age(> 60year old) groups based on their age. The clinical data of the subjects were reviewed, and analyzed based on their age.Results: With LT4 supplementation, there was no difference in free triiodothyronine (FT3), free thyroxine (FT4), and TSH levels among the three age groups. However, after approximately 4 weeks of LT4 withdrawal, the TSH levels of the three groups showed significant differences. The median stimulated TSH levels were 100, 83.1, and 64.6 mIU/L in the young, middle, and old age groups, respectively (P< 0.01). Moreover, the percentages of subjects, with TSH levels higher than 100 mIU/L, were 63.2%, 33.1%, and 12.9% (P< 0.01) in the young, middle, and old age groups, respectively. Spearman correlation analysis (R=− 0.42, P< 0.01) and partial correlation analysis (R=− 0.44, P< 0.01) revealed an inverse correlation between age and TSH levels after LT4 withdrawal.Conclusion: Aging plays an important role in TSH regulation. Age was inversely related to the stimulated TSH levels. The effect of senescence on TSH levels, as well as the underlying regulatory mechanisms, warrant further investigation.Keywords: aging, senescence, pituitary, thyroid